Perlindungan Hukum bagi pelaku Usaha dalam perjanjian kemitraan Waralaba: Studi kasus pemutusan kontrak Mitra Indomaret di Indonesia - Maatuil, Rexy Andalangi; Anggraeni Dalonto; Fernie Debrianty Manis; Sutrdya Anasthasya Tumunde; Paskahlina Indriyani Asmuruf; Debora Seilin Kasehung (Indo Publishing, 2025)
This study examines the legal protection provided to business actors engaged in franchise partnership agreements, focusing specifically on the issue of contract termination between Indomaret and its partners. In practice, franchise relationships often place partners in a weaker position due to limited access to information, dependence on franchisors’ operational systems, and an unequal bargaining position from the outset. These conditions frequently lead to disputes, especially when franchisors terminate agreements unilaterally or without a clear legal basis. The research employs a normative juridical approach enriched with case study analysis to assess the effectiveness of the Trade Law, franchise regulations, and principles of contract law in protecting partners. Normatively, Indonesian law provides several protective instruments, such as transparency obligations, fairness in drafting contract clauses, and restrictions against arbitrary actions by franchisors. However, implementation remains suboptimal due to franchisors’ dominance in contract drafting, weak government oversight, and limited capacity of partners to assert their rights through legal mechanisms. The Indomaret case study reveals significant imbalances in the distribution of rights and obligations, particularly regarding operational standards and performance evaluations. Therefore, the study highlights the need for stronger government supervision, more transparent and balanced contract arrangements, and improved legal literacy among partners to create a more equitable and proportional franchise partnership framework.